Analysis of Consumer Purchasing Decisions Influenced by Consumer Trust, Price Perception, and Product Quality (Case Study of the “Cicil Emas Galeri” Program at the Kejambon Tegal Branch of PT. Pegadaian Persero) - Irma Sholeha; Sari Wiyanti; Makmur Sujarwo (JURNAL ECONOMINA, 2026)
Gold is often viewed as a relatively safe asset for long-term investment. The focus of this study is to analyze the decline in purchase decisions for the “Cicil Emas Galeri” program at the Kejambon Tegal Branch of PT. Pegadaian PERSERO. This downward trend in purchases indicates a shift in consumer behavior, particularly regarding trust, price perceptions, and product quality assessments. This study employs both quantitative and qualitative research methods. The data used consists of primary data collected from respondents via questionnaires, utilizing non-probability sampling techniques and a purposive sampling method. The study population consisted of 1,325 individuals—all active users of gold services, programs, or installment plans at the Kejambon Tegal branch of PT. Pegadaian (Persero)—with a sample size of 100 respondents. The data were then processed and analyzed using classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination test). The results of the study showed that the third variable, Consumer Trust, with a significance value (0.000 < 0.05), had a positive effect on the Purchase Decision, meaning H1 is supported; Price Perception, with a significance value (0.000 < 0.05) has a positive effect on purchase decisions, meaning H2 is supported; Product Quality, with a significance value of (0.000 < 0.05), has a significant effect on purchase decisions, meaning H3 is supported. The variables of consumer trust, price perception, and product quality have a simultaneous effect on purchasing decisions, with a significance level of 0.000 < 0.05, meaning that Hypothesis 4 is supported.